2000
DOI: 10.1016/s0167-2789(99)00195-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear doubly diffusive convection in vertical enclosures

Abstract: Nonlinear doubly diffusive convection in two-dimensional enclosures driven by lateral temperature and concentration differences is studied using a combination of analytical and numerical techniques. The study is organized around a special case that allows a static equilibrium. The stationary states that bifurcate from this equilibrium are either symmetric or antisymmetric with respect to diagonal reflection. Local bifurcation analysis around the critical aspect ratio at which both modes appear simultaneously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
(94 reference statements)
1
23
0
Order By: Relevance
“…The supercritical branch of the bifurcating solution is only stable up to a pitchfork bifurcation at Ra = 542.4, following a scenario similar to that described in Ref. [12]. The interesting behavior in this system originates from the subcritical branch.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The supercritical branch of the bifurcating solution is only stable up to a pitchfork bifurcation at Ra = 542.4, following a scenario similar to that described in Ref. [12]. The interesting behavior in this system originates from the subcritical branch.…”
supporting
confidence: 61%
“…In this work we numerically study this latter configuration for a small Prandtl number binary mixture. We consider the case when thermal and solutal buoyancy forces exactly compensate each other, which allows the existence of a quiescent (conductive) state [10,11,12,13]. We have found that in this system there exists a large range of Rayleigh numbers in which the only stable solution is an orbit that features a low-frequency spiking behavior.…”
mentioning
confidence: 99%
“…They numerically showed that the primary instability of the equilibrium corresponds to a transcritical bifurcation point. The onset of oscillatory flow 7 and nonlinear bifurcation analysis 8,9 have been done and extensions of the configuration to an inclined cavity 10 and to a tilted porous cavity 11 have also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the primary instability of the equilibrium corresponds to a transcritical bifurcation point that is determined by Ra c ͑Le− 1͒, where Ra c is the critical Rayleigh number and Le is the Lewis number. The onset of oscillatory flow as a function of Le was studied by Ghorayeb et al 7 Nonlinear bifurcation analysis 8,9 has been done and extensions of the configuration to an inclined cavity 10 and to porous cavities 11,12 have also been considered. More recently, the situation in a three-dimensional enclosure was studied by Bergeon and Knobloch.…”
Section: Introductionmentioning
confidence: 99%